La planificación “del desarrollo” en Carlos Matus: una relectura - Celeste Viedma (Revista Iberoamericana de Estudios de Desarrollo)
With this article, it is aimed to produce a contribution to the studies on development and dependency from reading Carlos Matus. A series of similarities are established between Matus and the debates on development styles that occurred around the sixties and seventies in Latin America: a) the questioning of the growth rate as measure of development, b) the addressing the problem of dependency, c) the setting of objectives and feasibility calculation, and d) the considerations about a «planning crisis». In addition to the documentary analysis, findings concerning the itineraries of the figures involved are included.